John Hume and the revision of Irish nationalism. - McLoughlin, P. J. (Book collections on Project MUSE., 2010)
The book explores the politics of the most important Irish nationalist leader of his generation, and one of the most influential figures of twentieth-century Ireland: the Nobel Peace Prize winner, John Hume. Given his central role in the reformulation of Irish nationalist ideology, and the vital part which he played in drawing violent republicanism into democratic politics, the book shows Hume to be one of the chief architects of the Northern Ireland peace process, and a key figure in the making of the 1998 Good Friday Agreement. At the same time, it considers Hume?s failure in what he stated.